1989
DOI: 10.1002/bio.1170030206
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of phagocyte chemiluminescence using a microtitre plate luminometer

Abstract: The use of chemiluminescence techniques to study the interaction between bacteria and phagocytes has been useful for examining the extent to which serum factors, such as opsonins, are important in internalization of the organisms and the response of the cell to phagocytosed bacteria. However, such methods have been limited by the number of experiments which can be performed at one time using most commercial luminometers. However, the recent introduction of the Amerlite microtitre plate luminometer allows the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…If an agent is shown to have inhibitory actions on PMNL, it may have clinically useful antiinflammatory action in asthma. Previously, we have studied the effect of two commonly used beta-agonists, salbutamol and terbutaline on human PMNL function in vitro (4), using lucigenin-enhanced CL as a measure of phagocyte activity (14,15). In this study we investigated the effects of salmeterol on PMNL from normal (non-atopic) individuals in order to determine if its effect on such function in vitro differs in any way from conventional beta-adrenoceptor agonists.…”
Section: Ntro D U Ctlo Nmentioning
confidence: 99%
See 1 more Smart Citation
“…If an agent is shown to have inhibitory actions on PMNL, it may have clinically useful antiinflammatory action in asthma. Previously, we have studied the effect of two commonly used beta-agonists, salbutamol and terbutaline on human PMNL function in vitro (4), using lucigenin-enhanced CL as a measure of phagocyte activity (14,15). In this study we investigated the effects of salmeterol on PMNL from normal (non-atopic) individuals in order to determine if its effect on such function in vitro differs in any way from conventional beta-adrenoceptor agonists.…”
Section: Ntro D U Ctlo Nmentioning
confidence: 99%
“…CL assays were performed as described by Blair et al (15). Briefly, 50 pL of the PMNL suspension was added to triplicate wells of white microtitre strips (Dynatech Billingshurst, England) with 50pl of 5 x 10-mol/L lucigenin (Sigma) and 50p1 buffer with or without salmeterol.…”
Section: Chemiluminescence Assaymentioning
confidence: 99%
“…Apart from one-sample luminometers, other instruments are now being used to measure the respiratory burst of neutrophils, such as automated, PC-controlled multiple sample luminometers and, especially recently, microplate-based luminometers are increasingly used, allowing further miniaturization and automation of the procedure (7)(8)(9)(10). Although the determination of the metabolic activity of phagocytes, either in a vial-type luminometer or in a microplate-based luminometer alone, has been described by various authors, a direct comparison of the CL activity in identical samples of phagocytes measured in parallel using both types of the luminometers has been lacking up to now.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that microtitre plate CL readers such as the Amerlite CL reader are capable of measuring CL responses from large numbers of samples at once (Blair et al, 1988(Blair et al, , 1989 and we have now applied this technology to the study of monocyte activation.…”
Section: Introductionmentioning
confidence: 99%